Character Education Through Islamic Behavior Improvement (IBI) Among the Tourism Community in West Sumatra - Duski Samad; Suryadi Fajri; Annisa Fadnia; Wahidul Basri (AT-TA'LIM, 2023)
The development of halal tourism in West Sumatra is not proportional, due to a lack of service to tourists and the prevalence of negative social behaviors such as fraud, coercion, deception, and violence within the Minang society, often known as the 4P (Pakuak, Palak, Pakang, and Preman) behavior. This research aims to identify and educate on social behaviors of fraud, coercion, deception, and violence (Pakuak, Palak, Pakang, and Preman) that hinder the development of halal tourism in West Sumatra. The research findings indicate that first, the potential of halal tourism in West Sumatra, seen from religious, socio-cultural, natural potential, and stakeholder perspectives, strongly supports the development of halal tourism. Second, behaviors inhibiting the development of tourism communities, the 4P (Pakuak, Palak, Pakang, and Preman), are still prevalent amidst tourism activities in West Sumatra. Third, the Islamic Behavior Improvement (IBI) Tourism Model for tourism communities, tourists, and halal tourism stakeholders in West Sumatra, based on development results, has been tested for product validity. The validity level of the Islamic Behavior Improvement (IBI) Tourism Model book in terms of linguistic aspects, graphic design, and content feasibility is categorized as valid